A survey on squatter residents problems in Tabuan Foochow, Kuching/ Belenyun Medan … [et. al.] - Medan, Belenyun; Siba, Magdelene; David, Spencer Egat; Noet, Suwi; Jaret, Winie (2004)
Squatter problem is not a new phenomenon exist as a consequences of the development of the country and the economic growth of the country. This problem can be assumed as a “development diseases” if there are no measures taken to overcome to and can give a bad implication to our country. Squatter problems in Kuching is not new in our country but it already exist since early 1960's and at the moment it is still growing. Even though in reality, the squatter problem in Kuching is not that serious like in the Peninsular Malaysia especially in Kuala Lumpur and Penang, we are not supposed to react coldly towards this problem. Squatter in Sarawak especially in Kuching can be determined as a “bomb waiting to be exploded". Even though it cannot be denied that the existence of squatter now are getting dangerous and frightening the government. Therefore, it is important for the government to line up various sustainable plans and it must be conscientiously done. This study mainly being done in Tabuan Foochow area, as the squatter area exists for very long time without any concerned from the government. The objective of this study is to go deeply what are the factors causing the squatter problem and appropriate steps that government and the residents themselves should take to solve the problem arise in the squatter area.